Anti-N-methyl-d-aspartate receptor encephalitis in a patient with a 7-year history of being diagnosed as schizophrenia: complexities in diagnosis and treatment - Huang C (Dove Medical Press, 2015)
Chaohua Huang,1,2,4,* Yukun Kang,1,* Bo Zhang,1 Bin Li,1 Changjian Qiu,1 Shanming Liu,1 Hongyan Ren,1,2 Yanchun Yang,1 Xiehe Liu,1 Tao Li,1–3 Wanjun Guo1,21Mental Health Center, West China Hospital, Sichuan University, Chengdu, Sichuan, People’s Republic of China; 2State Key Laboratory of Biotherapy, Psychiatric Laboratory, West China Hospital, Sichuan University, Chengdu, Sichuan, People’s Republic of China; 3Mental Health Education Center, Sichuan University, Chengdu, Sichuan, People’s Republic of China; 4Mental Health Center, Affiliated Hospital of Luzhou Medical College, Luzhou, People’s Republic of China*These authors contributed equally to this workAbstract: Anti-N-methyl-d-aspartate receptor (NMDAR) encephalitis is a form of autoimmune encephalitis associated with antibodies against the NR1 subunits of NMDARs. Although new-onset acute prominent psychotic syndromes in patients with NMDAR encephalitis have been well documented, there is a lack of case studies on differential diagnosis and treatment of anti-NMDAR encephalitis after a long-term diagnostic history of functional psychotic disorders. The present study reports an unusual case of anti-NMDAR encephalitis. The patient had been diagnosed with schizophrenia 7 years earlier, and was currently hospitalized for acute-onset psychiatric symptoms. The diagnosis became unclear when the initial psychosis was confounded with considerations of other neurotoxicities (such as neuroleptic malignant syndrome). Finally, identification of specific immunoglobulin G NR1 autoantibodies in the cerebrospinal fluid and greater effectiveness of immunotherapy over antipsychotics alone (which has been well documented in anti-NMDAR encephalitis) indicated the diagnosis of anti-NMDAR encephalitis in this case. Based on the available evidence, however, the relationship between the newly diagnosed anti-NMDAR encephalitis and the seemingly clear, long-term history of schizophrenia in the preceding 7 years is uncertain. This case report illustrates that psychiatrists should consider anti-NMDAR encephalitis and order tests for specific immunoglobulin G NR1 autoantibodies in patients presenting with disorientation, disturbance of consciousness, cognitive deficit, dyskinesia, autonomic disturbance, or rapid deterioration, even with a seemingly clear history of a psychiatric disorder and no specific findings on routine neuroimaging, electroencephalography, or cerebrospinal fluid tests in the early stage of the illness.Keywords: anti-N-methyl-d-aspartate receptor encephalitis, schizophrenia, differential diagnosis, treatment